Augmented Reality: A New Learning Experience among Health Care Professionals - Masood Jawaid; Zubair Ahmed Siddiqui; Anum Sohail Siddiqui; Muhammad Usman Karim (BioMedica, 2021)
Background and Objective: Augmented Reality (AR) is an effective tool for learning as well as marketing with multilateral interactive communication. It allows brands to give their customers unique experiences with the convenience of tapping into their mobile devices. This study was conducted to assess the perceptions of healthcare professionals (HCPs) to learn through AR and its effectiveness in HCPs’ engagement and learning experience. Methods: An interventional study was conducted with HCPs across various tertiary care hospitals in Pakistan from May 2020 till December 2020. An AR based activity was carried out with the HCPs where they used pictures of objects around them to create a message. These were geo-tagged to a question related to hypertension and participants answered each question. Mobile application – WallaMe was utilized for this activity. At the end of the activity, HCPs were requested to fill a feedback form based on their experience with the AR app. Data was entered and analyzed by using SPSS version 22. Results: AR stimulated learning  gives the participants an overall exciting (80%), captivating (81%), and fruitful learning experience (82%). AR for marketing campaign was more effective for Brand Recall with paper based campaign for 82.8% and more effective than digital campaign for 85.6% participants. AR was recommended by 80% participants for learning and brand recall. Conclusion: AR is a useful tool to enhance user experience for learning as well as improves brand recall and can be used for marketing campaigns.